A survey test in reading in Pilipino for grade six Waray learners - Agner, Soledad (Giban) 1939- ([Quezon City publisher not identified], 1971)
This is a survey test in reading in Pilipino in second language situation. This test has been especially designed for grade six Waray learners of Pilipino of Kapangian Community School, Tacloban District II, Tacloban City and other schools in Waray-speaking regions. It is the purpose of this study to get a general picture of the reading abilities and skills as well as the reading problems of grade six Waray learners of Pilipino so that appropriate measures for improvement of the total reading program could be made.
Thesis (Master in Education)--University of the Philippines.
Keywords: Reading; Pilipino language -- Study and teaching -- Bisayan students